Embryo Selection with Preimplantation Chromosomal Screening in Patients with Recurrent Pregnancy Loss - Shahine, Lora K.; Lathi, Ruth B. (Seminars in Reproductive Medicine, 2014)
Recurrent pregnancy loss (RPL) is a multifactorial disorder which is often challenging for both patients and providers. Guidelines for the evaluation and treatment of patients with RPL include screening for uterine abnormalities, parental chromosomes, and antiphospholipid antibodies, but approximately half of RPL patients remain unexplained. The current recommendation for patients with unexplained RPL is expectant management which offers most patients a 60 to 80% success rate over time. Genetic imbalances in the embryo, including inherited unbalanced translocations and de novo aneuploidy, are frequent causes of miscarriage. Preimplantation genetic screening (PGS) has been proposed as an effective method for selecting viable embryos for transfer that may result lower risk of miscarriage for patients with unexplained RPL and carriers of balanced translocations. The current evidence examining the use of in vitro fertilization with PGS in patients with RPL reveals variable results, due to differences in technologies used and variable patient populations. Newer approaches, which include blastocyst biopsy and the ability to screen for all 24 chromosomes, show the most promise in reducing miscarriage rates. Studies that identify which patients are most likely to benefit from PGS and include live birth rates per initiated cycles are needed before universally recommending this treatment to couples with RPL.
Keywords: miscarriage; recurrent pregnancy loss; preimplantation genetic screening; aneuploidy; translocation; chromosome screening